Shaping Future Leaders: Exploring Challenges and Strategies in Character Education at Madrasah Tsanawiyah - Surani, Surani; Darmawangsa, Andi; Ardi, Ardi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to gain a deep understanding of character education management and the supporting and inhibiting factors in the implementation of Character Education Management at Madrasah Tsanawiyah Pesantren Mizanul Ulum. This research employs a qualitative approach with a case study design. Data collection is conducted through in-depth interviews with various stakeholders, including the school principal, teachers, and parents. Participatory observation is also carried out to understand the daily dynamics in the madrasah. Thematic analysis is applied to identify supporting and inhibiting factors in character education implementation. The results reveal that full involvement of the pesantren community such as regular meetings with parents and open classes for parents, integrated curriculum such as material development and collaborative projects in class, and active character guidance are the main supporting factors. Conversely, challenges from external environments, resource limitations, and technological impacts emerge as inhibiting factors. Wise and creative management steps in overcoming resource limitations, coupled with a prudent technological approach, have proven effective in maintaining focus on shaping students' characters.